Predictors of Science Performance of Grade Six Pupils in Sablayan North District - Daligues, Joffrey (International Journal of Sustainability and Advanced Integrated Research, 2026)
Predictors of science performance are either examined alone or focus only on psychosocial factors of the pupils without considering the association of the other core subjects. This study examined the relationship of the learner-centered factors, attitude toward science, pupil engagement in science, and interest toward science, combined with the two core academic subjects, English and Mathematics performance, with Science performance of Grade 6 pupils to identify which among these five factors predicts Science performance. A descriptive-correlational research design was used in this study. The 211 Grade 6 pupils of Sablayan North District enrolled in the School Year 2025-2026 were the respondents of the study selected through proportional stratified random sampling from a population of 432 pupils across five selected schools in the district. The data used in learner-centered factors were gathered and analyzed using survey questionnaires with a 5-point Likert scale, while academic performances were obtained from the advisers’ class records and analyzed using the prescribed grading scale of the Department of Education’s policy for classroom assessment. Generally, the study revealed that pupils have a positive attitude, a high level of engagement and interest in science, driven by positive perceptions, active participation, and classroom experiences in science class. Although attitude, engagement, and interest toward science are significantly related to science performance, the relationships are weak. The factors that remain remarkably and consistently significant across written works, performance tasks, and quarterly assessments are cognitive attitude, emotional engagement, situational interest, and scientific curiosity, which play an important role in achieving higher performance in science, whereas other factors do not show consistent correlation. On the other hand, Mathematics and English performance have a strong and consistent association with Science performance. The study identified the English performance along with the Mathematics performance as the strongest predictors of Science performance. The findings of the study revealed that acquired numeracy and literacy skills incarnated with the learner are stable long-term skills that can be transferred into a science context and help the students perform at their best.